Kotimaiset tieteelliset julkaisusarjat ja avoimuus - Linna Anna-Kaarina; Holopainen Mika; Ikonen Arto; Ylönen Irene (Informaatiotutkimuksen yhdistys, 2022)
This study examines open access availability and self-archiving policies of 336 Finnish peer reviewed journals and serials which are classified at levels 1 to 3 in national Publication Forum. The study concludes that 53 % of Finnish peer reviewed publication channels are open access and 12 % of non-open access publication channels have defined their green open access policy to allow self-archiving. 6 % of publications practice delayed open access model and 2 % hybrid model. The study also concludes that only a small group of Finnish peer reviewed journals meet the focal Plan S requirements.